2010
DOI: 10.1007/s00467-010-1703-y
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of PPAR-γ agonist and ARB in treatment of experimental IgA nephropathy

Abstract: Our recent in vitro study demonstrated peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist potentiated the anti-inflammatory effect of angiotensin receptor blocker (ARB) in tubular epithelial cell under milieu mimicking IgA nephropathy (IgAN). Here we studied the therapeutic effect of combining a PPAR-γ agonist, rosiglitazone (Ros), with an ARB, losartan (Los), in experimental IgAN induced in Lewis rats by oral and intravenous immunization with bovine gamma-globulin (BGG). The rats were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…As no ddY mouse was available in China, we used the animal IgAN model in which a direct antigenic stimulus to esophageal endothelial mucosal cells activates local and migratory macrophages was based on our previous studies [28] . Data from other studies have also shown that this method can build a good stable animal model for IgAN [29,30] . IgAN was induced by continuous oral immunization with 0.1% BSA (G7516, Sigma Chemical Co., St. Louis, Mo., USA) with 6 m M HCl in tap water for 10 weeks, followed by tail intravenous injection of 1 mg BSA daily for 3 successive days.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…As no ddY mouse was available in China, we used the animal IgAN model in which a direct antigenic stimulus to esophageal endothelial mucosal cells activates local and migratory macrophages was based on our previous studies [28] . Data from other studies have also shown that this method can build a good stable animal model for IgAN [29,30] . IgAN was induced by continuous oral immunization with 0.1% BSA (G7516, Sigma Chemical Co., St. Louis, Mo., USA) with 6 m M HCl in tap water for 10 weeks, followed by tail intravenous injection of 1 mg BSA daily for 3 successive days.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Data from other studies also have shown that this method can build a stable animal model for IgAN [28][29][30] . IgAN was induced by continuous oral immunization with 0.1% BSA (G7516, Sigma Chemical Co., St. Louis, Mo., USA) with 6 m M HCl in tap water for 10 weeks, followed by tail intravenous injection of 1 mg BSA daily for 3 successive days.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…[21][22][23] For the control group, saline replaced the BGG. The IgAN model was established at the end of the 12th week.…”
Section: Establishment Of the Igan Modelmentioning
confidence: 99%